The new era in U.S. national security an introduction to emerging threats and challenges - Jarmon, Jack A. 1951- (Rowman & Litlefield, 2014)
The New Era in U.S. National Security focuses on the emerging threats of the second decade of the 21st century, well after 9/11, and well into the age of globalization. It is a thorough, technically competent, survey of the current arena of conflict and the competition for political and economic control by state and non-state actors. Starting with the current national security establishment, it discusses the incompatibility between the threats and the structure organized to meet them. It then looks at the supply chain, including containerization and maritime security as well as cybersecurity, terrorism, and transborder crime networks. The last section of the book focuses on existing industrial and defense policy and the role the private sector can play in national security. Pulling together different areas, such as the logistics of the supply chain, the crime-terrorist nexus, and cyberwarfare, the book describes the landscape of today's new battlefields. It shows how the logistics of asymmetrical warfare, the rise of the information age, the decline of the importance and effectiveness of national borders, the overdependence on fragile infrastructures, and the global reach of virtual, paramilitary, criminal, and terrorist networks have created new frontlines and adversaries with diverse objectives. This core text for international security, strategy, war studies students is technical yet accessible to the non-specialist. It is a timely and comprehensive study of the realities of national security in the United States today.